Improving Performance Using 2 X 2 Single Element Massive Mimo Antenna in 6G Devices - Sundresan Perumal; Kumutha Duraisamy; S. Parathasarathi; P. Gobi; T. Lakshmi; R. Kokila Devi (Sumy State University, 2026)
Non-Indexed Publication